2018
DOI: 10.1016/s1872-2067(18)63153-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the support on cobalt carbide catalysts for sustainable production of olefins from syngas

Abstract: Co2C-based catalysts with SiO2, γ-Al2O3, and carbon nanotubes (CNTs) as support materials were prepared and evaluated for the Fischer-Tropsch to olefin (FTO) reaction. The combination of catalytic performance and structure characterization indicates that the cobalt-support interaction has a great influence on the Co2C morphology and catalytic performance. The CNT support facilitates the formation of a CoMn composite oxide during calcination, and Co2C nanoprisms were observed in the spent catalysts, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The direct production of olefins via syngas conversion is an alternative process for the production of key chemical building blocks from non-petroleum-based sources. More and more studies focus on the improvement of catalytic performance with high selectivity to lower olefins (C 2–4 = ) directly from syngas. , Recently, based on the concept of OX-ZEO bifunctional catalysis, Jiao et al reported that a composite catalyst (ZnCrO x/ MSAPO) affording two types of active sites with complementary properties could reach C 2–4 = selectivity as high as 80% . Cheng et al also found that the coupling of methanol-synthesis and methanol-to-olefins reactions with a bifunctional catalyst (ZnZrO x/ SAPO-34) can realize the direct conversion of syngas to lower olefins with high selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…The direct production of olefins via syngas conversion is an alternative process for the production of key chemical building blocks from non-petroleum-based sources. More and more studies focus on the improvement of catalytic performance with high selectivity to lower olefins (C 2–4 = ) directly from syngas. , Recently, based on the concept of OX-ZEO bifunctional catalysis, Jiao et al reported that a composite catalyst (ZnCrO x/ MSAPO) affording two types of active sites with complementary properties could reach C 2–4 = selectivity as high as 80% . Cheng et al also found that the coupling of methanol-synthesis and methanol-to-olefins reactions with a bifunctional catalyst (ZnZrO x/ SAPO-34) can realize the direct conversion of syngas to lower olefins with high selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Co 2 C can be used instead of Cu component as the active site for CO nondissociative adsorption, and the Co/Co 2 C interface acts as dual active sites for alcohol formation. The appropriate proportion of Co/Co 2 C was considered to show profound influence on selectivity and stability. , In our previous work, an effective strategy was developed by tuning chemical environment and synergistic relay reaction to promote the production of higher alcohols . It was found that the highly dispersed Rh δ+ or Ru δ+ species facilitated the stable existence of Co 2 C and catalyzed the coupling of syngas and in situ generated olefins to produce extra oxygenates via hydroformylation.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing serious shortage of petroleum resources, it is necessary to make full use of alternative nonpetroleum feedstocks. Syngas (CO/H 2 ) can be generated from a variety of carbon-containing sources including coal, biomass, and natural gas. Fischer–Tropsch synthesis (FTS) is a promising technology for the conversion of syngas to fuels and chemicals. However, the main products of FTS are mostly linear paraffins with a broad Anderson–Schulz–Flory distribution. , For the purpose of high selectivity to value-added chemicals (such as olefins, alcohols, and aromatics) during the syngas conversion process, development of new catalyst systems is highly desirable . Aromatics are important chemical raw materials, mainly used as monomers for the production of various polymers such as polystyrene, phenolic resins, and so forth. , Aromatics can also be used as additive to increase the octane number of gasoline.…”
Section: Introductionmentioning
confidence: 99%